Territorial conflict and environmental (in)justice:: the case of the construction of the Southern Expressway in the Pirajubaé Marine Resex, Santa Catarina, Brazil - Spínola, Juliana Lima; Teixeira, Cristina Frutuoso; Andriguetto-Filho, José Milton (Sustainability in Debate, 2018)
This article analyzes the situation of environmental injustice and conflict arising from the construction of an expressway across the territory of the Marine Extractive Reserve (Resex) of Pirajubaé in the municipality of Florianópolis, southern Brazil. For this, a documentary analysis and semi-structured interviews with Resex extractivists and ICMBio officials were carried out. It was observed that the meanings and interests related to the appropriation and use of the territory of the Resex established a situation of environmental injustice for those involved in sustainable extractivism activities and were also the object of the conflict between the "extractivists", public authorities and the business sector involved in the execution of the work, including the mandatory environmental licensing. The economic interests prevailed over the environmental control and the interests of the "extractivists" who resisted the construction of the expressway. Although the existence of a Resex does not prevent situations of environmental injustice and territorial conflicts, it is relevant to their confrontation by the extractivists.